The ZIP Transporter Family Member OsZIP9 Contributes To Root Zinc Uptake in Rice under Zinc-Limited Conditions. Issue 3 (5th May 2020) - Huang, Sheng; Sasaki, Akimasa; Yamaji, Naoki; Okada, Haruka; Mitani-Ueno, Namiki; Ma, Jian Feng
Abstract : The zinc transporter OsZIP9, expressed at the exodermis and endodermis of root mature region, contributes to Zn uptake from soil in rice. Abstract: Zinc (Zn) is an important essential micronutrient for plants and humans; however, the exact transporter responsible for root zinc uptake from soil has not been identified. Here, we found that OsZIP9, a member of the ZRT–IRT-related protein, is involved in Zn uptake in rice ( Oryza sativa ) under Zn-limited conditions. OsZIP9 was mainly localized to the plasma membrane and showed transport activity for Zn in yeast ( Saccharomyces cerevisiae ). Expression pattern analysis showed that OsZIP9 was mainly expressed in the roots throughout all growth stages and its expression was upregulated by Zn-deficiency. Furthermore, OsZIP9 was expressed in the exodermis and endodermis of root mature regions. For plants grown in a hydroponic solution with low Zn concentration, knockout of OsZIP9 significantly reduced plant growth, which was accompanied by decreased Zn concentrations in both the root and shoot. However, plant growth and Zn accumulation did not differ between knockout lines and wild-type rice under Zn-sufficient conditions. When grown in soil, Zn concentrations in the shoots and grains of knockout lines were decreased to half of wild-type rice, whereas the concentrations of other mineral nutrients were not altered. A short-term kinetic experiment with stable isotope 67 Zn showed that 67 Zn uptake in knockout lines was much lower than that in wild-type rice. Combined, these results indicate that OsZIP9 localized at the root exodermis and endodermis functions as an influx transporter of Zn and contributes to Zn uptake under Zn-limited conditions in rice.